The dog family - Harvey, Bev (Harvey, Bev. Animal families., 2004)
Simple text compares and contrasts members of the dog family in terms of where they live, body features, eating habits, and size. Species featured include foxes, African hunting dogs, dingoes, coyotes, black-backed jackals, gray wolves, and domestic dogs.